PEMAKNAAN SIMBOLIK ATAS PENGUKURAN NILAI ASET INFRASTRUKTUR - Syarif Syahrir Malle; Veronika Sari Denka; Muhammad Disyacita Tosa (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine the meaning of symbolic interactionism in determining the method of evaluating infrastructure assets in supporting the fairness of financial statements. This qualitative research uses a critical approach to the analysis unit of the Makassar City Public Works Department. Methods of collecting data with interview techniques and other secondary data support. The data analysis technique refers to the interactive model. The results of the study found that the agency had carried out the assessment method correctly and correctly. The valuation of infrastructure assets uses cost, but the valuation of land assets is carried out at fair value. Symbolization is done through three aspects of analysis, namely syntax, semantics and pragmatics. This symbolizing method provides benefits for users and supports the fairness of financial statements so that they get an unqualified opinion from BPK.